Elastic modulus and hardness of CaTiO3, CaCu3Ti4O12 and CaTiO3/CaCu3Ti4O12 mixture - Ramirez, M. A. [UNESP]; Parra, R.; Reboredo, M. M.; Varela, José Arana [UNESP]; Castro, M. S.; Ramajo, L. (Elsevier B.V., 2010)
Three ceramic systems, CaTiO3 (CTO), CaCu3Ti4O12 (CCTO) and intermediate nonstoichiometric CaTiO3/CaCu3Ti4O12 mixtures (CTO.CCTO), were investigated and characterized. The ceramics were sintered at 1100 degrees C for 180 min. The surface morphology and structures were investigated by XRD and SEM. Elastic modulus and hardness of the surfaces were studied by instrumented indentation. It was observed that CCTO presented the higher mechanical properties (E = 256 GPa, hardness = 10.6 GPa), while CTO/CCTO mixture showed intermediate properties between CTO and CCTO. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: CaTiO3; CaCu3Ti4O12; Elastic modulus; Hardness; Nanoindenter